(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the impact of industrial development in the Sirdaryo region on visual arts, particularly within the landscape genre. It examines the significance of the concept of industrial-natural landscapes formed by the integration of industrial facilities with the natural environment, highlighting its compositional, coloristic, and aesthetic dimensions. Additionally, the study briefly explores the artistic representation of labor and modernization, as well as the role of this theme in art education.